Nickel acetylacetonate as decomposition catalyst for HTPB-based fuels: Regression rate enhancement effects. (1st December 2021) - Yu, Hongsheng; Chen, Suhang; Yu, Xiaodong; Zhang, Wei; Paravan, Christian; DeLuca, Luigi T.; Shen, Ruiqi
Graphical abstract: Highlights: Nickel acetylacetonate enhances the regression rate of HTPB by catalyzing its pyrolysis. The catalytic effect is mainly induced by Ni 2+ and NiO. Ni(acac)2 decreases the combustion heat and causes accumulation of decomposition products. Abstract: The slow regression rate induced by the difficulty of pyrolysis has limited the practical application of hydroxyl-terminated polybutadiene (HTPB)-based fuels for hybrid rocket propulsion. A possible strategy is the use of suitable transition metal elements promoting polymer matrix thermal decomposition of fuels. This paper investigates the effects of nickel acetylacetonate, Ni(acac)2, on the thermal stability and combustion of HTPB-based fuel formulations. The presented experimental results show that the addition of Ni(acac)2 can intensely decrease the thermal stability of HTPB thus enhancing the solid fuel regression rate even at a small additive mass fraction: under an oxygen mass flux of 50 kg/m 2 s, HTPB + 5 wt% Ni(acac)2 shows a 25.5% increase over the non-loaded baseline. Kinetics analyses reveal that the catalytic effect is mainly induced by the Ni 2+ in Ni(acac)2 at the early stage of decomposition, and by the NiO produced from the oxidative decomposition of Ni(acac)2 in the fuel final degradation stage. On the other hand, the addition of Ni(acac)2 decreases the combustion heat of HTPB-based fuels significantly and implies the accumulation of its decomposition products (much metal Ni, moderate elemental C, and a little NiO.) at the fuel regressing surface. Eventually, when the content of Ni(acac)2 exceeds 5 wt%, the growth of regression rate slows down rapidly, and a performance detriment occurs at 40 wt%. This study verifies the catalytic effect of Ni(acac)2 on polymer matrix for HTPB based fuels showing the attractive regression rate performance of this additive.